A Double-Blind, Randomized Controlled Trial of Soy versus Estrogen in Alleviating Post-Menopausal Vasomotor Symptoms - Hanif, Shafaq; Zia, Mohsina Saeed; Shakil, Mohsin (International Journal of Pathology, 2018)
Introduction: Estrogen therapy has long been prescribed to treat menopausal symptoms. It has been extensively studied,and it is the most consistently effective therapy for vasomotor symptoms. Soy has been investigated, mainly over the past 10years, because of their potential effects on the health of postmenopausal women.Objectives: To compare the efficacy of soy and estrogen in alleviating post-menopausal vasomotor symptomStudy Design: Randomized controlled trial.Materials & Methods: A total of 122 post-menopausal women, 40 to 65 years of age were included. Patients on hormonereplacement therapy, tamoxifen or receiving chemotherapy/radiation therapy or taking any dietary supplements wereexcluded. Then selected patients were placed randomly into Group A (estrogen) & Group B (soy), by using lottery method.Patients were called for follow up after 12 weeks and data was collected of the number of hot flushes average per day andefficacy.Results: The mean age of women in group A was 52.82 ± 6.08 years and in group B was 52.09 ± 6.90 years. The mean hotflushes/day in group A was 2.56 ± 1.19 and in group B was 2.85 ± 1.25. There was 50% post-treatment reduction in hot flushesas compare to number of hot flushes average per day at pre treatment in 57 (93.44%) patients in Group A (Estrogen) while inGroup B (Soy), it was seen in 46 (75.41%) patients with p-value of 0.006.Conclusion: This study concluded that use of estrogen therapy was more effective in alleviating post-menopausal vasomotorsymptom compared to soy therapy.